Adaptive Structural Model Development for Off-campus Student Housing Preferences using SEM – PLS Analysis - Mohd, Thuraiya; Johari, Noraini; Islamiah Abdullah Sani, Suwaibatul; Abdullah, Lizawati; Ahmad @ Mohamed, Nurulanis (International Journal of Engineering and Technology, 2019)
The immense number of student enrolment has created high demand for student accommodation far exceeding the available on-campus student accommodation provided by universities and colleges. Thus, some students may need to reside off-campus instead. As different groups of society have different preferences and needs, it is crucial to identify the off-campus student housing preferences who are the economically determinant group of people. This paper presents the formulation of a structural model depicting off-campus student   housing preferences. The study presents data collected through a survey conducted via structured questionnaires in likert scale type of questions distributed randomly among off-campus students in selected public and private universities located within the State of           Selangor. The data was analysed using the SEM – PLS. The results from analysis indicate that the four main factors to be considered relating to student housing preferences are: housing environment, location, housing quality, and housing accommodation. Findings of this research will provide a set of guidelines for off-campus student housing preferences that is significant to local authorities, housing developers, Higher Education Institutions (HEIs), students' societies, and also the local communities to be the panacea for                  studentification issues.
Keywords: Structural Model; Off-Campus Housing Preference; Students Housing Preferences; SEM-PLS Analysis